Use of transesterified 1,3-diketoesters in the synthesis of trisubstituted pyrazoles and their biological screening - M. G. Dhonde; N. T. Khati; M. Idrees; N. J. Siddiqui (Bulletin of the Chemical Society of Ethiopia, 2013)
Starting from 2-acetylbenzofuran derivatives 1a-d, methyl/ethyl 4-substituted/unsubstituted benzofuran-2-yl)-2,4-dioxobutanoate 2a-d and 3a-d have been synthesized by Claisen’s condensation reaction with diethyloxalate. The transesterified product, 1,3-diketoester 2a-d on condensation with phenyl hydrazine undergo cyclization to afford the corresponding methyl 5-(substituted/unsubstituted benzofuran-2-yl)-1-phenyl-1H-pyrazole-3-carboxylate 4a-d, which upon further condensation with hydrazine hydrate yielded 5-(substituted/unsubstituted benzofuran-2-yl)-1-phenyl-1H-pyrazole-3-carbohydrazide 5a-d. The structures of the newly synthesized compounds 2a-d, 3a-d, 4a-d and 5a-d were characterized by their elemental analysis and spectral studies such as IR, 1H NMR, 13C NMR and MS. All the synthesized compounds were screened for their antimicrobial activity. Most of the synthesized compounds showed high sensitivity against the selected bacteria and fungi at various concentrations.DOI: http://dx.doi.org/10.4314/bcse.v27i1.9